ECO-INNOVATION IN COASTAL SEAFOOD MSMES: SUSTAINABLE PROCESSING STRATEGIES AND INFORMATION TECHNOLOGY INTEGRATION TO PROMOTE THE CIRCULAR ECONOMY - Ridha Taurisma Lajaria; Ghalib Suprianto; Arsyad Junaiddin; I Putu Raditya; Muh. Aqlil Unggil (Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2025)
This study examines the application of eco-innovation in micro, small, and medium enterprises (MSMEs) of seafood in coastal areas as a sustainable processing strategy integrated with information technology to encourage a circular economy. This sector has great potential in supporting the economic welfare of coastal communities, but faces challenges in the form of technological limitations, inefficiency of production processes, and low added value of products due to traditional processing practices. The purpose of this research is to analyze how the application of environmentally friendly innovation and digital transformation can improve business efficiency, competitiveness, and sustainability in the context of the circular economy. The research approach used is quantitative with a case study strategy on seafood processing MSMEs, using primary data obtained through questionnaires and analyzed with descriptive statistics. The results show that the adoption rate of eco-innovation is positively correlated with increased raw material efficiency, reduction of production waste, and improvement of product quality. Information technology integration, especially in supply chains and digital marketing, plays a catalyst in accelerating the implementation of sustainable innovation and expanding market access. This research provides a theoretical contribution to the development of a digital-based eco-innovation model in the maritime sector as well as a practical contribution to strengthening policies and strategies for empowering coastal MSMEs to realize an inclusive and sustainable circular economy.